Investigating social factors affecting academic ranking and providing a comprehensive model - Namaki, Ali; Ghourchian, Nadergholi; Jafari, Parivash (Social Determinants of Health, 2018)
Background: A new competitive factor between universities is the production of knowledge, in which the material benefits are gained. Competition in achieving such a situation has created the new systems of ranking and evaluation of universities. The purpose of the present study was to present an appropriate model for university ranking and to evaluate the effectiveness of social factors in the final ranking model. Methods: First, the indexes of 29 global ranking systems were studied and analyzed using content analysis method. Then, an interview was conducted with faculty members and the model was presented through theme analysis and open coding. A questionnaire was designed for the study and to confirm the reliability of the questionnaire, Cronbach’s alpha coefficient was used. Also, the validity of the questionnaire was confirmed using the expert opinions. Convergent validity technique was also used using Amos graphics software Results: The importance of social factors affecting academic ranking was obtained through calculation of the means. Based on our results, the importance of the factors from the largest to the smallest was as follows: 1. educational performance 2. research performance 3. entrepreneurship and employment 4. scientific rank, national and international image, and 5. the ability of the university to meet the needs of the society. All of which show moderate to high levels. Conclusion: Based on the results, the calculated values of fitness indices were in desirable range and the proposed model for the ranking of universities was suitable with empirical data and enjoys a favorable situation.